Pengaruh Komunikasi dan Pendelegasian Wewenang terhadap Kinerja Pegawai pada Kantor Kecamatan Luwuk Kabupaten Banggai - Pakaya, Syaiful (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2021)
This study aims to determine how much influence communication and delegation of authority have on employee performance at the Luwuk District Office, Banggai Regency. Collecting main data is through a list of statements that are tested through validity and reliability tests. The analysis method used is the path analysis method. The first test results show that the communication variable (X1) and delegation of authority (X2) simultaneously have a positive and significant effect on employee performance at the Luwuk District Office, Banggai Regency, which is 97.9%. The results of testing the second hypothesis show that communication (X1) partially has a positive and significant effect on the performance of employees at the Luwuk District Office, Banggai Regency, which is 25.9%. The third test results show that the variable delegation of authority (X2) partially has a positive and significant effect on employee performance at the Luwuk District Office, Banggai Regency, which is 74.8%.